The Protective Effect of Artocarpus altilis Leaf Extract on Rat Models of Diethylene Glycol-Induced Hepatotoxicity - Jatmiko Susilo; Bambang Purwanto; Muchsin Doewes; Dono Indarto (Indonesian Journal of Pharmacy, 2024)
Diethylene glycol (DEG) is an alcohol derivative, which is metabolized into toxic products and is one of the main causes of liver disease. This paper aims to determine the hepatoprotective effect of AA by analyzing the levels of MDA, AST, ALT, and liver hypertrophy in the DEG-induced rat model. Twenty-five male rats were divided into 5 groups: normal, DEG (0.75% v/v), AA1 (DEG + AA 100 mg/kg BW), AA2 (DEG + AA 200 mg/kg BW), and AA3 (DEG + AA 400 mg/kg BW). Rats were given DEG for 28 days ad libitum, and AA was administered from days 14 to 28 orally. Twenty-eight days later, serum levels of MDA, ALT, AST, and liver hypertrophy were determined. DEG induction increased body weight and liver hypertrophy, levels of MDA, ALT, and AST, and decreased the AST/ALT ratio, whereas treatment with AA was shown to reverse to normal conditions which were observed for 28 days depending on the dose of AA (p < 0.05). We conclude that treatment with AA is an effective therapeutic option as a hepatoprotector in a rat model induced by DEG in a dose-dependent manner. Future challenges need to be developed as prospective complementary drugs or phytopharmaceuticals.